2010
DOI: 10.3109/19396368.2010.489660
|View full text |Cite
|
Sign up to set email alerts
|

Critical Aspects of Detection of Sperm DNA Fragmentation by Tunel/Flow Cytometry

Abstract: Despite the many studies documenting an increase of sperm DNA damage in subfertile and infertile subjects, determining whether this parameter is relevant for the clinic is still an open question. Indeed, results of clinical investigations on sperm DNA damage and outcome of ART procedures are often conflicting as many factors affect the predictive power of these tests. The techniques used to reveal such damage is one of these factors. Techniques detecting sperm DNA damage are indeed numerous and heterogeneous. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 67 publications
2
13
0
1
Order By: Relevance
“…The variation of the correlation coefficient between the studies may result from the design of the study (the type and number of patients) and the use of different protocols for each assay, especially in the case of the TUNEL assay where no standard clinical protocol exists. Moreover, it was shown that the values obtained when measuring TUNEL‐positive cells manually by fluorescence microscopy were lower than the one obtained using flow cytometry analysis (reviewed in (Muratori et al ., )).…”
Section: Discussionmentioning
confidence: 94%
“…The variation of the correlation coefficient between the studies may result from the design of the study (the type and number of patients) and the use of different protocols for each assay, especially in the case of the TUNEL assay where no standard clinical protocol exists. Moreover, it was shown that the values obtained when measuring TUNEL‐positive cells manually by fluorescence microscopy were lower than the one obtained using flow cytometry analysis (reviewed in (Muratori et al ., )).…”
Section: Discussionmentioning
confidence: 94%
“…A number of different factors such as preparation, fixation and permeabilization of samples negatively affect its clinical application (Muratori et al, 2010). The latter factor is due to the highly compact nature of sperm chromatin by and its reinforced structure in protamines due to inter-and intramolecular bonds (Balhorn et al, 1992;Brewer et al, 2003;Vilfan et al, 2004), which prevent TdT from directly accessing the DNA strand breaks.…”
Section: The Tunel Assaymentioning
confidence: 99%
“…However, this specificity has neither been demonstrated for spermatozoa (Manicardi et al, 1998) nor can this endpoint be used because it can also be reached by other mechanisms such as necrosis. Thus, by using the TUNEL assay, one should rather refer to this DNA damage as 'DNA fragmentation' than 'apoptosis' (Henkel et al, 2004;Muratori et al, 2010).…”
Section: The Tunel Assaymentioning
confidence: 99%
“…Thus, the influence of semen quality and age on the predictive power of sDF is currently unknown. In addition, the lack of standardization of most methods (22) used to detect sDF hampers the clinical use of the reported threshold values. Our group has developed a new version of flow cytometric terminal deoxynucleotide transferase-mediated dUTP nick-end labeling (TUNEL) combining nuclear staining with propidium iodide (PI) for the detection of sDF and yielding precise, standardized (23), and more accurate measurements compared with simple TUNEL (24).…”
mentioning
confidence: 99%